2015
DOI: 10.1177/0004867415581022
|View full text |Cite
|
Sign up to set email alerts
|

A model for managing the mentally ill fixated person at major events

Abstract: This novel diversionary model for assessing and intervening with concerning, fixated persons at major events proved effective in mitigating the risk posed by these individuals. It also highlighted the need for police, security and mental health services to consider the fixated in major event planning, for the safety of the event, the public and vulnerable mentally ill, fixated persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It fulfilled similar functions for royal weddings and for other major events. Similarly, the Queensland FTAC was involved in security planning and operations for the G20 summit in Brisbane 61 and for the 2018 Commonwealth Games.…”
Section: Further Activitiesmentioning
confidence: 99%
“…It fulfilled similar functions for royal weddings and for other major events. Similarly, the Queensland FTAC was involved in security planning and operations for the G20 summit in Brisbane 61 and for the 2018 Commonwealth Games.…”
Section: Further Activitiesmentioning
confidence: 99%
“…Threat management teams also offer advice and training in relation to this unusual area of practice, giving presentations to police forces and mental health services, sharing best practice and being involved with the planning of large events (Pathé 2015). Hoffmann & Sheridan (2008) observed that historically there was little sympathy for celebrity victims of stalking, that in some way this behaviour ‘goes with the territory’ and they should endure it.…”
Section: Issues Arising At Ftac When Effecting An Intervention In the Ukmentioning
confidence: 99%
“…18 The effectiveness of QFTAC in managing the risk at major public figure gatherings in Queensland was demonstrated during subsequent events including a Royal Visit to Queensland in April 2014 and the G20 World Leaders' Summit in Brisbane in November 2014. 19…”
Section: Queensland Fixated Threat Assessment Centre (Qftac)mentioning
confidence: 99%